Bleeding assessment in haemophilia carriers—High rates of bleeding after surgical abortion and intrauterine device placement: A multicentre study in China. Issue 1 (19th November 2019) - Li, Sen; Fang, Yunhai; Li, Li; Lee, Adrienne; Poon, Man‐Chiu; Zhao, Yongqiang; Zhang, Xinsheng; Wang, Shujie; Cheng, Yan; Li, Kuixing
Abstract: Introduction: An increased bleeding tendency has been shown in female haemophilia carriers compared to healthy females. Bleeding assessment tools (BATs) have mainly been performed in western cultures. It is unclear how they perform in populations with different healthcare, health/wellness concepts and awareness, as well as family planning practices. Aim: To (a) describe and compare the bleeding symptoms in carriers with healthy females, particularly for bleeding after surgical abortion and intrauterine device (IUD) placement which are performed frequently for family planning in China; (b) quantify scores of International Society on Thrombosis and Haemostasis Bleeding Assessment Tool (ISTH‐BAT) and Chinese‐BAT (C‐BAT) developed to include surgical abortion and IUD placement as separate categories in Chinese haemophilia carriers; (c) correlate bleeding scores (BS) with factor levels. Methods: We conducted a multicentre, cross‐sectional study on obligate haemophilia carriers and healthy controls using ISTH‐BAT and C‐BAT. Results: We enrolled 125 haemophilia carriers and 106 controls. Carriers, compared to controls, had significantly higher median BS (3 vs 1 by both ISTH‐BAT and C‐BAT) and lower factor level (63.5 vs 101.8 IU/dL). Bleeding after surgical abortion and IUD placement was significantly associated with carrier status. Bleeding scores from neither ISTH‐BAT nor C‐BAT showed significant correlation with factor levels. Conclusion: Haemophilia carriers in China experienced abnormal bleeding. Unique to the Chinese carriers is significant bleeding after surgical abortion (3rd highest incidence of bleeding symptom) and IUD placement (4th highest). However, both ISTH‐BAT and C‐BAT exhibited no correlation between BS and factor levels in this population and neither could identify carriers with low factor level (of <50 IU/dL).